ASSESSMENT OF THE INTERRELATION OF VARIOUS FACTORS OF INFLUENCE ON CLINICAL, NEUROLOGICAL, INSTRUMENTAL AND PSYCHOEMOTIONAL INDICATORS OF CHILDREN WITH BRONCHIAL ASTHMA - Djurabekova Aziza Tokhirovna; Samatov Farrukh Farhodovich; Amonova Zahro Kahramonovna (Scholar Express Journals, 2024)
Bronchial asthma occupies a rather high place among noncommunicable diseases of children and adolescents. Thus, the statistical register for recent years has revealed that among children of Uzbekistan under 14 years of age, the prevalence of bronchial asthma is 18.3 and 64.2 (per 100000 children), and among adolescents 23.3 and 92.8 (per 100000 adolescents) respectively, with a tendency to increase by 10-30%.
Keywords: bronchial asthma; children; clinical and neurological indicators